Factors Affecting Paddy Rice Production in Tanggetada District Kolaka Regency - Aan Wilhan Juliatmaja; Nursalam Nursalam; Helviani Helviani (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2021)
The aim of this research is to find out what factors affect lowland rice production in Tanggetada district, Kolaka regency and to find out how the level of technical efficiency, allocative efficiency and economic efficiency of rice lowland in Tanggetada district, Kolaka regency. To examine the effect of the utilization of the factors of production used on the yield of lowland rice production, a multiple linear regression is used and to determine the level of economic efficiency from the use of the factors of production. production by switching between technical efficiency and price / allocative efficiency and any input factors. The results of the study indicated that the factor of production of land area, urea fertilizers and NPK fertilizers had a significant effect. Meanwhile, labor-intensive factors of production, nararel pesticides and seeds have no significant effect. and Based on the results of the allocative efficiency analysis, an average value of 3.18 was obtained. This means that it is not allocatively efficient, so it is necessary to add the use of factors of production and it is necessary to maximize the profits obtained by making efficiency in the cost elements of the factors of production in order to '' achieve optimal conditions. At the same time, the results of technical efficiency show that lowland rice cultivation is not technically efficient. so the use of factors of production should be added to increase the efficiency of lowland rice cultivation. And the value of economic efficiency shows that lowland rice cultivation is still not efficient. It is therefore necessary to make changes and increase the capacity to combine existing factors of production through training in order to achieve economic efficiency.